Distribution of Abnormal Number of Teeth and Gender Differences: A Sample of Al-Muthanna University Students Aged 18-24 Years Old - Hayder Saad Hanfoosh1, Osamah Mohammed Aldaghir1, Arkan Muslim Alazzawi2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Congenital or developmental missing teeth (Hypodontia) is one of important numerical anomalies of teeth. So that many subject field have been carry out in different element of the humans, to find the prevalence of hypdontia. Hyperdontic dentition are teeth that appear in plus to the regular number of teeth.This review was planned to assess the distribution of abnormal number of teeth decreased (hypodontia), increased (hyperdontia) and gender differences.This review was applied from 23 /10/ 2016 to 12 /4/ 2019 on 1971 (1065 males, 906 females) students in four colleges in Al-Muthanna University were College of medicine (294), College of dentistry (299), College of pharmacy (185) and college of economics (1193) were clinically examined, only (202) of them had abnormal number of teeth and subjected to orthopanto-mograms to detect the missing teeth and extra teeth. Their age was ranging from 18 to 24 years.The abnormal number of teeth in (10.2%) students. Hypodontia in (9.18%) students. The hypodontia of maxillary lateral incisor in (34.8%) students followed by hypodontia in mandibular second premolar (30.9%) students. The hyperdontia in maxillary and mandibular teeth (1.06%) students. Mesiodens in (0.7%).The study displays that about (10.2%) students had abnormal of teeth number. Hypodontia happens more often than hyperdonti. The foremost repeatedly absent tooth was maxillary lateral incisor and the second one was the mandibular second bicuspid. About hyperdontia, the most frequently hyperdontic tooth was Mesiodens. All of them, difference between gender was non-significant.